A systematic review of graph query language operators for graph analytics - F. Vasconcelos, Felipe; Catarin, Renan B.; J. Coutinho, Fábio; Halfeld-Ferrari, Mirian; Aguiar, Cristina Dutra (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais do XLI Simpósio Brasileiro de Bancos de Dados, 2026)
Graph analytics has gained significant relevance in recent years, enhancing the expressiveness of graph data systems by enabling advanced analytics within declarative query systems. In this context, graph query language operators have emerged to bridge the gap between graph processing and declarative querying. However, to the best of our knowledge, no prior work surveys advances in this area. We conduct a systematic review of graph query language operators for graph analytics, outlining their evolution, and classifying studies into five categories: domain-specific solutions, graph pattern matching and querying, graph mining, temporal graph analytics, and fuzzy and approximate querying. Finally, we discuss limitations, trends, and research opportunities.